1993
DOI: 10.1016/0376-7388(93)85269-3
|View full text |Cite
|
Sign up to set email alerts
|

Permporometry study on the size distribution of active pores in porous ceramic membranes

Abstract: Permporometry as well as nitrogen adsorption-desorption techniques have been applied to study the pore size distribution in y-alumina membranes with a pore radius ranging from about 2 nm to 10 nm. The permporometry technique measures the active pores only, while nitrogen adsorption-desorption measures the active as well as the passive pores. The pore size distribution in the porous ceramic membrane supported with an cy-alumina substrate (supported membrane) was determined by using permporometry, while the memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 9 publications
0
40
0
2
Order By: Relevance
“…Consequently, gas physisorption analysis of supported membranes is not possible because the amount of top-layer material is much to small, and the relative influence of the mesoporous support is, therefore, strong. Permporometry, which is a relatively new technique for pore size analysis of supported membranes [7,8], can not be applied for microporous systems, since the thickness of the t-layer [9] exceed the size of the micropores (t-layer is adsorption layer of liquid used for permporometry).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, gas physisorption analysis of supported membranes is not possible because the amount of top-layer material is much to small, and the relative influence of the mesoporous support is, therefore, strong. Permporometry, which is a relatively new technique for pore size analysis of supported membranes [7,8], can not be applied for microporous systems, since the thickness of the t-layer [9] exceed the size of the micropores (t-layer is adsorption layer of liquid used for permporometry).…”
Section: Introductionmentioning
confidence: 99%
“…A pore size for the c-alumina intermediate layer of 3-5 nm was determined by permporometry, using the method as described elsewhere [35].…”
Section: Methodsmentioning
confidence: 99%
“…separation of dewaxed oil from MEK/toluene mixtures or the de-acidification of vegetable oils) the extensive, but reversible, swelling of PDMS in organic solvents limits its utility in some apolar solvents because of a decrease in selectivity, due to an increase in free space between polymer chains. Swelling has been identified as a key problem in the performance of PDMS membranes for organic-organic separations [27,[61][62][63][64][65][66][67][68]. For example, for hydrophobic membranes Van der Bruggen et al [69] found lower solute rejection when hexane was used as solvent when compared with separations involving alcohols and water as solvent and they proposed that this was due to the interaction between membrane and solvent.…”
Section: Polymeric Membranes As Snrfmentioning
confidence: 99%
“…Permporometry [61] was employed to determine the pore size distribution of the modified and unmodified membrane layers. A detailed description is given in chapter 5.…”
Section: Permporometrymentioning
confidence: 99%